2019
DOI: 10.3324/haematol.2018.208819
|View full text |Cite
|
Sign up to set email alerts
|

A novel combinatorial technique for simultaneous quantification of oxygen radicals and aggregation reveals unexpected redox patterns in the activation of platelets by different physiopathological stimuli

Abstract: The regulation of platelets by oxidants is critical for vascular health and may explain thrombotic complications in diseases such as diabetes and dementia, but remains poorly understood. Here, we describe a novel technique combining electron paramagnetic resonance spectroscopy and turbidimetry, which has been utilized to monitor simultaneously platelet activation and oxygen radical generation. This technique has been used to investigate the redox-dependence of human and mouse platelets. Using selective peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 50 publications
5
49
0
Order By: Relevance
“…36 By contrast, the few available studies using the full peptides Aβ40 and Aβ42 are incomplete and have generated controversial results on their effective ability and potency to trigger platelet responses. 11,14,15,19 The current incompleteness and incongruences are reasonably because amyloid peptides tend to form fibrils in aqueous solutions, with specific intrinsic kinetics, and the implications of their biochemical conformation on biological activities was not properly considered. Amyloid Aβ fibrils are present in atherosclerotic plaques, and Aβ peptides are also detected in the circulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 By contrast, the few available studies using the full peptides Aβ40 and Aβ42 are incomplete and have generated controversial results on their effective ability and potency to trigger platelet responses. 11,14,15,19 The current incompleteness and incongruences are reasonably because amyloid peptides tend to form fibrils in aqueous solutions, with specific intrinsic kinetics, and the implications of their biochemical conformation on biological activities was not properly considered. Amyloid Aβ fibrils are present in atherosclerotic plaques, and Aβ peptides are also detected in the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had reported that Aβ42, but not Aβ40, promotes the formation of ROS in platelets, through the activation of NADPH oxidase NOX1 and NOX2. 14,15 However, in these studies, the chemical form of the peptides was not characterized. Therefore, we recon- Intracellular ROS production was then evaluated in flow cytometry, as described in the Methods.…”
Section: Fibrillar Amyloid Peptides Promote Ros Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] NADPH oxidases (NOXs) are important sources of ROS in platelets [5][6][7] and their function promotes platelet activation. 8,9 NOXs are a family of multimeric plasma membrane complexes generating the majority of non-mitochondrial ROS in mammalian cells. Each complex consists of a catalytic subunit and a number of regulatory subunits responsible for the maturation, stabilization, haem incorporation, and translocation to the cell membrane of the enzymatically functional complex.…”
Section: Introductionmentioning
confidence: 99%
“…Although platelet NOX2 has been investigated, 4 the expression of NOX1 in human platelets has only been described relatively recently. 10 Despite the established importance of NOXs in the molecular mechanisms leading to platelet activation, 8,9,11 the exact role of different NOX isoenzymes, and the molecular mechanism linking NOX activity to platelet regulation remains uncertain. 9,[12][13][14] Nonetheless, a convincing amount of evidence suggests that the enzymatic activity of NOXs plays a significant role in promoting platelet responses.…”
Section: Introductionmentioning
confidence: 99%